2011
DOI: 10.1080/02640414.2010.531752
|View full text |Cite
|
Sign up to set email alerts
|

When the chips are down: Effects of attributional feedback on self-efficacy and task performance following initial and repeated failure

Abstract: In two experiments, we manipulated the controllability and stability of causes of failure and explored the impact of these factors on self-efficacy and performance. In Experiment 1, participants (N = 80; mean age 20.03, SD 1.03 years) were provided with false negative feedback following performance on a blindfolded dart throwing task. Consistent with theory and recent research, an induced belief that failure was beyond control and unlikely to change led to lower These findings suggest that in novel circumstanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…Although the relationship between team attributions and future team performance remains relatively unexplored (Reimer, 2001;Wang, 1994) good support is available for a causal link between attributions and subsequent performances of individuals (Coffee & Rees, 2011;Martin-Krumm, 25 Sarrazin, Peterson, & Famose, 2003;Orbach, Singer, & Murphey, 1997). In short, we expect approach motivating attributions to facilitate quality of training and subsequent team performance, and avoidance motivating attributions to debilitate quality of training and subsequent team performance.…”
Section: Behavioural Consequencesmentioning
confidence: 90%
See 1 more Smart Citation
“…Although the relationship between team attributions and future team performance remains relatively unexplored (Reimer, 2001;Wang, 1994) good support is available for a causal link between attributions and subsequent performances of individuals (Coffee & Rees, 2011;Martin-Krumm, 25 Sarrazin, Peterson, & Famose, 2003;Orbach, Singer, & Murphey, 1997). In short, we expect approach motivating attributions to facilitate quality of training and subsequent team performance, and avoidance motivating attributions to debilitate quality of training and subsequent team performance.…”
Section: Behavioural Consequencesmentioning
confidence: 90%
“…Our goal here is not to provide a detailed description of each of these relationships (as this can be inferred from Figure 1) but rather to illustrate the value of such research designs for evidence-based practice. Studies of individual sport performers have shown that self-efficacy mediates the relationship between attributions and behaviour intentions (Spink & Nickel, 2009), attributions and performance goals (Tolli & Schmidt, 2008), and attributions and future performance (Coffee & Rees, 2011;). It would therefore seem reasonable that interventions targeting performance improvement should attempt to foster attributions that facilitate high levels of self-efficacy.…”
Section: Mediating Relationshipsmentioning
confidence: 99%
“…The content of the intervention was based on Bandura's Social Learning Theory, assuming that self-efficacy should be considered not as a personality trait but rather as a contextdependent concept (Bandura, 1977(Bandura, , 1982, which means that it can be manipulated as shown in social psychology and sport studies (Coffee & Rees, 2011). Social Learning Theory holds that SEBs are rooted in individual factors (e.g.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…The content of Confident Parents was based on Bandura's social learning theory, assuming that self-efficacy should be considered not as a personality trait, but rather as context-dependent, which means that it can be manipulated, as shown in social psychology and sport studies [53]. Social learning theory holds that self-efficacy is rooted in individual factors (e.g., personal history of accomplishment, emotional arousal and its physiological impact) as well as in contextual factors (e.g., verbal feedback from others, social comparisons), [54].…”
Section: The Confident Parents Programmentioning
confidence: 99%